2019
DOI: 10.1038/s41563-018-0265-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-resonance features of destructive quantum interference in single-molecule thiophene junctions achieved by electrochemical gating

Abstract: Controlling the electrical conductance and in particular the occurrence of quantum interference in single-molecule junctions through gating effects, has potential for the realization of highperformance functional molecular devices. In this work, we used an electrochemically-gated, mechanically-controllable break junction technique to tune the electronic behaviour of thiophene-based molecular junctions that show destructive quantum interference (DQI) features. By varying the voltage applied to the electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
183
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 214 publications
(192 citation statements)
references
References 34 publications
(46 reference statements)
4
183
0
2
Order By: Relevance
“…Quantum interference (QI) offers the unique opportunity to tune charge transport through molecular devices and materials, [1] which leads to various applications such as QIbased thermoelectrics, [2] molecular memory, [3] molecular transistors, [4] and sensors. [5] Them olecular building blocks play avital role in investigating QI-based molecular junctions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum interference (QI) offers the unique opportunity to tune charge transport through molecular devices and materials, [1] which leads to various applications such as QIbased thermoelectrics, [2] molecular memory, [3] molecular transistors, [4] and sensors. [5] Them olecular building blocks play avital role in investigating QI-based molecular junctions.…”
mentioning
confidence: 99%
“…
Molecular components are vital to introduce and manipulate quantum interference (QI) in charge transport through molecular electronic devices.Uptonow,the functional molecular units that show QI are mostly found in conventional p-a nd s-bond-based systems;i ti st hus intriguing to study QI in multicenter bonding systems without both p-a nd sconjugations.N ow the presence of QI in multicenter-bondbased systems is demonstrated for the first time,t hrough the single-molecule conductance investigation of carborane junctions.W ef ind that all the three connectivities in carborane frameworks showdifferent levels of destructive QI, which leads to highly suppressed single-molecule conductance in para-and meta-connected carboranes.T he investigation of QI into carboranes provides ap romising platform to fabricate molecular electronic devices based on multicenter bonds.Quantum interference (QI) offers the unique opportunity to tune charge transport through molecular devices and materials, [1] which leads to various applications such as QIbased thermoelectrics, [2] molecular memory, [3] molecular transistors, [4] and sensors. [5] Them olecular building blocks play avital role in investigating QI-based molecular junctions.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It further proves that the structural change of the molecule junction, gate voltage, and QI effects could be affecting each other. Studies using MCBJ techniques have also shown that molecular conductance can be extensively adjusted by changing the voltage applied to the electrochemical gate at room temperature . This work provides the most direct experimental basis for charge transfer controlled by antiresonance generated by destructive quantum interference of gate pressure regulation.…”
Section: Optimization Strategies For Ote Devicesmentioning
confidence: 86%
“…b) Schematic illustration of the chemical structure of 2,4‐TP‐SAc and 2,5‐TP‐SAc. The measured conductance under sweep potentials between −0.4 and 1.0 V. Reproduced with permission . Copyright 2019, Springer Nature.…”
Section: Optimization Strategies For Ote Devicesmentioning
confidence: 99%